Amorphous aluminum-oxide supercapacitors. (28th September 2018) - Fukuhara, Mikio; Kuroda, Tomoyuki; Hasegawa, Fumihiko; Hashida, Toshiyuki; Kwon, Eunsang; Konno, Kazuya
Abstract: An amorphous aluminium-oxide supercapacitor can store a large amount of electric charge on its blackish, uneven Al2 O3− x surface, which has a convexity of 21 nm, AlO6 clusters, and a resistivity of . The electric storage can be elucidated by extremely enhanced electron trapping resulting from both the quantum-size effect and the offset effect of the positive charges at O-vacancy sites. Here, a supercapacitor, characterised by a high surface area of and the formation of large numbers of electric double layers, demonstrates a vertical line in the Nyquist diagram, corresponding to rapidly increased imaginary impedance and phase angle of with decreasing frequency in the Bode diagram using a distributed constant-electric circuit with a parallel assembly of nanometer-sized capacitors on a highly insulating amorphous aluminium surface. The supercapacitor indicates a switching effect for both positive and negative potentials. Thus, we can apply rechargeable dry solid supercapacitors in place of practical Li ions.